FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PEGAWAI PUSKESMAS SRAGEN PADA MASA PANDEMI COVID-19 - Galuh Wulansari; Bambang Wahyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The impact of the COVID-19 pandemic directly has an impact on the decline in the performance of health services, one of which is the role of puskesmas in carrying out their duties and functions. This problem occurs in the Sragen Health Center. The performance achievement at the Sragen Health Center was 65.62% and was included in the less category, it was proven that it had not reached the target targeted by the government of 80%. The problem that arises is is there a relationship between perceptions of the COVID-19 pandemic with the performance of the Sragen Health Center employees in 2021. This type of research is quantitative with a cross sectional study approach. The population in this study were all employees of the Sragen Public Health Center. Sampling used a total sampling technique, so the research sample was 56 respondents. Based on the analysis using the chi-square test, it shows that work attitude has a relationship with the performance of the p-value of 0.003 (p-value <0.005), and there is a positive correlation in the direction of the strength of the moderate correlation with the Pearson correlation value of 0.423. Work motivation has a relationship with the performance of the p-value of 0.002 (p-value <0.005), and there is a positive correlation in the direction of the moderate strength of the correlation with the Pearson correlation value of 0.405. Work experience has a relationship with the performance of the p-value of 0.001 (p-value <0.005), and there is a positive correlation in the direction of the strength of the strong correlation with the Pearson correlation value of 0.621. The work environment has a significant relationship with the performance of the p-value of 0.001 (p-value <0.005), and there is a positive correlation in the direction of the moderate strength of the correlation with the Pearson correlation value of 0.494.Keywords: performance, environment, motivation, experience, attitude